Ferramentas tecnológicas para detecção de fadiga no controle de tráfego aéreo: uma revisão de literatura - MIRANDA, Jailmar Oliveira (Universidade Federal do Oeste do Pará, 2024)
This research aims to analyze the trends in the use of different technologies applied to detect fatigue in air traffic controller activities, describing the peculiarities of this professional activity, and also, analyzing the fatigue factor, which nowadays has become prominent as a public health concern. Mental fatigue reduces the alertness and ability of the air traffic controller, causing a decrease in the effectiveness and safety of carrying out their tasks, considering that the human factor is one of the determining factors in cases of incidents occurring. and air traffic accidents, even if unintentional, then, we sought to carry out a bibliographical survey on practical applications of technologies applied to the detection of fatigue in air traffic workers, in the SciELO and Google Scholar databases, between 2017 and 2022. The work seeks to find technologies that can mitigate and preventively achieve the harmful effects caused by fatigue, evaluating work carried out in that area, as well as in similar areas, where technology applications are viable and aligned in common aspects. However, it is possible to use these techniques, such as those seen in this work, which were: face monitoring, physiological variables and vocal extraction; and that the combination of techniques brings an even more accurate result in fatigue detection. It is worth highlighting that the work covered requires a detailed study to explore the feasibility of large-scale adoption of the technologies developed to date.